2007
DOI: 10.1007/s11661-007-9372-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Behavior of CuZr-Based Glassy Alloys at 400 °C to 500 °C in Dry Air

Abstract: The oxidation behavior of the Cu 47.5 Zr 47.5 Al 5 (Cu3) and Cu 47 Ti 34 Zr 11 Ni 8 (Cu4) bulk metallic glasses (BMGs) was studied over the temperature range of 400°C to 500°C in dry air. The oxidation kinetics of both alloys generally followed a multistage parabolic-rate law, and the steady-state parabolic-rate constants (k p values) fluctuated with temperature for the Cu3 BMG, but increased with increasing temperature for the Cu4 BMG. The scales formed on the BMGs were strongly dependent on the temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…The CZA4-BMG was prepared by an injection-casting technique, described elsewhere [11] . The average composition in atomic percent for the CZA4-BMG, analyzed by X-ray wavelength-dispersive spectroscopy (WDS), contained 45.03% Cu, 45.10% Zr, and 4.94% Al, and 4.93% Ag.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CZA4-BMG was prepared by an injection-casting technique, described elsewhere [11] . The average composition in atomic percent for the CZA4-BMG, analyzed by X-ray wavelength-dispersive spectroscopy (WDS), contained 45.03% Cu, 45.10% Zr, and 4.94% Al, and 4.93% Ag.…”
Section: Methodsmentioning
confidence: 99%
“…It is interesting to note that the k p values of the CZA4-BMG progressively increase with the temperature when it is below 450 8C, while a significant lower k p value is obtained at 500 8C, which corresponds to a slower scaling rate. For comparative purposes, the k p values of the CZA3-BMG obtained previously [11] are also summarized in the same table. Obviously, the steady-state k p values of the CZA4-BMG are slightly lower than those of the CZA3-BMG at T 425 8C.…”
Section: Oxidation Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Minor amounts of m-ZrO 2 were observed at high temperatures (420-460°C) but absent at low temperatures (330-390°C). The formation of m-ZrO 2 was commonly seen in the high-temperature (above T g ) oxidation of Zr-based metallic glass [18,19]. The structures of substrates were also examined.…”
Section: Oxidation Kineticsmentioning
confidence: 99%
“…Oxidation behavior of Zr-based metallic glasses has been examined by several authors . Especially interesting results have been obtained for the Zr-CuAl ternary alloys (Ref [16][17][18] in which the inversion of oxidation kinetics is observed, as well as strong dependence of the scale composition on the temperature. Kai et al (Ref 17,18) reported a non-intuitive dependence of Al 2 O 3 formation process on the concentration of Al in the alloy.…”
Section: Introductionmentioning
confidence: 94%